Issues of Teaching Practice in Master of English Education: Supervisors’ Perspectives - Kadel, Purna Bahadur (Tribhuvan University Journal, 2023)
This study analyse on the issues of teaching practice through the lenses of internal supervisors. It is an attempt to explore whether the pre-service teachers were provided with adequate comments and feedbacks from their supervisors during on-campus and off-campus activities; whether the assigned tasks were appropriate for them and what challenges of teaching practice existed in Master of English Education. Phenomenological research design was adopted to carry out hits study. Ten English teachers were selected non-randomly from constituent and affiliated colleges of Tribhuvan University as a sample to elicit data to address the research questions of this study. The findings of this study showed that there were lack of proper feedbacks and comments both from their peers and supervisors; teaching practice has been taken as rituals; the pre-service teachers could be engaged professionally through proper management of teaching practice; the main root causes of being ineffective of teaching practice were lack of proper exposure of item construction and analysis, inadequate amount of remuneration to supervisors. It is concluded that the course of teaching practice under the Faculty of Education should be revamped and revisited in order to produce competent efficient and professional English teachers in both content and pedagogical techniques.